1 0 x 2 − 2 α ( x y ) + y 2 + 1 0 x + 2 y − β = 0 represents a pair of lines that intersect at the y − a x i s . Find the value of ∣ α ∣ + ∣ β ∣ .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Point of intersection of two lines represented by
a x 2 + 2 h x y + b y 2 + 2 g x + 2 f y + c = 0 is
( h 2 − a b b g − h f , h 2 − a b a f − g h )
U can easily prove it by partial differentiating the equation wrt x and wrt y, and then solving the equations obtained.
Since they meet at y-axis . Let the point be ( 0 , t )
So h 2 − a b b g − h f = 0
b g = h f
→ 1 × 5 = − α × 1
α = − 5
Substituting x = 0 in the given equation
y 2 + 2 y − β = 0
Since the lines intersect at a common point , so the above quadratic equation must have equal roots .
D = 0
4 − 4 × ( − β ) = 0
β = − 1
Since they intersect at y axis while putting x=0 remaining quadratic in y must have equal roots. Hence beta=-1 Now applying condition for a second degree equation to be a pair of straight lines i.e. abc+2fgh-af^2-bg^2-ch^2=0 We get quadratic in alpha . Solving we get alpha=-5
Great observations to eliminate the variables!
Problem Loading...
Note Loading...
Set Loading...
Let the two straight lines be: { y = m 1 x + c 1 = 0 y = m 2 x + c 2 = 0
Since they intersect at the y -axis: ⇒ c 1 = c 2 = c . Therefore, we have:
1 0 x 2 − 2 α x y + y 2 + 1 0 x + 2 y − β = ( m 1 x − y + c ) ( m 2 x − y + c ) = m 1 m 2 x 2 + ( m 1 + m 2 ) x y + y 2 + c ( m 1 + m 2 ) x + 2 c y + c 2
Equating the coefficients on both sides:
⎩ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎧ m 1 m 2 = 1 0 m 1 + m 2 = − 2 α c ( m 1 + m 2 ) = 1 0 2 c = 2 c 2 = − β . . . ( 1 ) . . . ( 2 ) . . . ( 3 ) . . . ( 4 ) . . . ( 5 )
⎩ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎧ ( 4 ) : ( 5 ) : ( 3 ) : ( 2 ) : c = 2 2 = 1 β = − c 2 = − 1 ( m 1 + m 2 ) = 1 1 0 = 1 0 α = − 2 m 1 + m 2 = − 5
⇒ ∣ α ∣ + ∣ β ∣ = ∣ − 5 ∣ + ∣ − 1 ∣ = 6